THE ONE NATION ONE ELECTION CONUNDRUM: EVALUATING PROSPECTS AND CHALLENGES IN INDIA - Nidhi Singh (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
The ‘One Nation, One Election’ (ONOE) concept in India proposes simultaneous elections at all governance levels, aiming to streamline the electoral process and reduce expenditure. The strengths include potential cost savings, reduced policy paralysis due to frequent election cycles and increased governance efficiency and many others. However, the weaknesses lie in the logistical challenges of conducting nationwide elections and the risk of undermining regional political dynamics etc. There are yet many opportunities including the enhanced voter participation and the promotion of a more issue-based political discourse. Yet, it is not without threats which involves the possible dilution of the federal structure and the marginalization of regional parties. The democratic conundrum arises from the tension between potential administrative efficiency benefits and the preservation of the pluralistic, multi-tiered nature of Indian democracy. The research paper dwells into understanding the ONOE concept which requires careful scrutiny and inclusive dialogue, considering the diverse political philosophies that shape India’s vibrant democracy. The paper includes the challenge in striking a balance between electoral pragmatism and the democratic principle of representation. While theoretically appealing, the ONOE concept poses practical challenges that need to be addressed through comprehensive dialogue and deliberation, ensuring that any electoral process reform upholds the principles of federalism, representation, and inclusivity integral to India’s democratic fabric.